Tinjauan Literatur: Penerapan Model Pembelajaran Berbasis Proyek untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa pada Pembelajaran Biologi SMA - Miranda, Sonya; Hardinah, Nur Ayu; Melisa, Atika Okta (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Creative thinking ability is one of the essential competencies of the 21st century that needs to be instilled in biology learning. however, many studies show that conventional approaches have not been effective in developing students’ creative thinking skills. This study aims to preliminary research data on project-based learning models in improving students’ creative thinking skills in biology learning through a literature review. The research method used a literature study with the help of prism in analyzing 12 relevant scientific articles, published between 2020 and 2025, from various scientific journals/articles, and books. The analysis was conducted based on the implementation, effectiveness, and impact of project-based learning models on creative thinking skills. The results of the review show that the project-based learning model is able to significantly improve students’ creative thinking skills through activities that involve exploration, problem analysis, and application of biological concepts relevant to real life. In addition, the project-based learning model is also be able to encourage collaborative and develop communication skills. The application of project-based learning model is very effective in learning because it provides meaningful and relevant learning experiences by involving students directly in learning. The conclusions obtained from the 12 articles analyzed provide the same statement and evidence that the application of project-based learning models has significant potential in improving creative thinking skills in biology learning.